Reverberation multi-source localization algorithm based on compressed sensing with dual microphones - Yi ZHANG; Juan LI; Min ZHANG (Tongxin xuebao)
In traditional multi-source localization field,it is necessary to guarantee that the number of microphone is more than the number of source.To overcome this constraint,a dual-microphone multi-source localization algorithm based on CS was proposed,where the number of sound source localized successfully was more than 3.The multi-source localization was regarded as the block sparse signal reconstruction in this algorithm,and the full room impulse responses normalized were exploited to construct the compressed observation matrix in frequency domain.In reconstructed block sparse signal,the positions of non-zero blocks were corresponded to the positions of sound sources in space.The simulation shows that compared with the SRP-sub algorithm,in reverberation time 0.6s with dual-microphone,the proposed multi-source localization algorithm based on compressed sensing has higher capability which can reach 80% success rate by using 40 frequency points to localize 3 sound sources.